Peningkatan Hasil Belajar Luas Bangun Datar melalui Strategi Belajar Kooperatif Tipe Jigsaw bagi Siswa Kelas V SD Negeri 02 Silaut Kecamatan Silaut - Masril Masril (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
This research is motivated by the fact that elementary schools that learning is often dominated by teachers as a source of information and learning models used are generally conventional, so that the learning process is less attractive to students, and learning outcomes are less satisfying. From that, the researcher through this class action research wanted to improve the results of Mathematics learning through Jigsaw type cooperative learning for the fifth-grade students of SDN 02 Silaut. The results of this study can be concluded that through Jigsaw, cooperative learning can improve student mathematics learning outcomes in class V SDN 02 Silaut District Silaut. Therefore, it is recommended that teachers can carry out the learning process through Jigsaw cooperative learning in order to improve student learning outcomes and interests.